The Role of the Professional Teacher as the Agent of Change for Students - Mas'ud Muhammadiah; Andi Hamsiah; Abdurrohman Muzakki; Zain Ahmad Fauzi; Nuramila Nuramila (STAI Hubbulwathan Duri, 2022)
Teachers are one of the main factors for success in education. The teacher is an agent of change to students. The purpose of this study is to use a literature review approach to gain insight into the systematic mapping review for the article under consideration. A literature review, one of the main reasons for the importance of a professional teacher who becomes an agent of change for his students. Methods in this study using the literature review method by searching various sources from Google Scholar, Scopus, WOS and also Erics. The results of this study are that being a professional teacher is required. The teacher's professional attitude is manifested in the form of being able to control oneself, which is expressed through a spiritual mental attitude, so that he always acts based on moral values, principles of life, and behaves religiously in accordance with his religion and belief in carrying out his duties.